Neutrosophic Rhotrices for Improved Diagnostic Accuracy through Score Rhotrix Computation - Florentin Smarandache; Ananda Priya B; Gnanachandra P; Saeid Jafari (Neutrosophic Sets and Systems)
We introduce neutrosophic rhotrices, which serve as a novel extension of neutrosophic matrices. The primary objective is to establish the foundational structure for neutrosophic rhotrices and to define crucial operations that can be performed on them. We explore the concept of neutrosophic rhotrices in depth, outlining the fundamental operations necessary for their effective manipulation. Furthermore, we investigate the essential properties of neutrosophic rhotrices utilizing these newly established operations. In addition, we provide an algorithm designed to enhance decision-making processes in medical diagnostics, supported by an illustrative example to clarify its application.